13C-Pattern of Natural Glycerol: Origin and Practical Importance - Weber, D.; Kexel, H.; Schmidt, H.L.
The average ä13C-value of glycerol from plant origin is 4-5
Keywords: CARBON-13; GLYCEROL; ISOTOPIC PATTERN; STABLE ISOTOPES; WINE